Relationship between autonomic nervous function and cognitive function in elderly patients with Parkinson's disease - JI Li; YANG Ning; LIU Wei‑guo; JI Li (Chinese Journal of Contemporary Neurology and Neurosurgery, 2024)
Objective To analyze relationship between autonomic nervous function and cognitive function in elderly patients with Parkinson's disease (PD). Methods A total of 130 elderly patients with PD admitted to The Affiliated Brain Hospital of Nanjing Medical University from January 2020 to December 2022 were included. Hoehn‑Yahr staging was used to evaluate stage of the disease, Unified Parkinson's Disease Rating Scale Ⅲ (UPDRS Ⅲ) was used to evaluate the severity of motor disorders, Scales for Outcomes in Parkinson's Disease ‑ Autonomic (SCOPA ‑ AUT) was used to evaluate autonomic nervous function, Mini‑Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA) were used to evaluate cognitive function, Non‑Μotor Symptoms Scale (NMSS) was used to evaluate the severity of nonmotor symptoms. Results According to whether the patients were accompanied by Alzheimer's disease (AD), they were divided into a group with AD (n = 82) and a group without AD (n = 48). The proportion of Hoehn‑Yahr staging 3 to 5 (χ2 = 5.689, P = 0.017), UPDRSⅢ score (t = 21.490, P = 0.000), SCOPA‑AUT score (t = 21.330, P = 0.000), dysregulation of body temperature (χ2 = 8.512, P = 0.004), urinary dysfunction (χ2 = 17.270, P = 0.000), gastrointestinal dysfunction (χ2 = 24.471, P = 0.000), dysregulation of pupil (χ2 = 5.299, P = 0.021), cardiovascular dysfunction (χ2 = 15.355, P = 0.000) and NMSS score (t = 32.309, P = 0.000) in the group with AD were higher than those in the group without AD, the MMSE (t = 4.730, P = 0.000) and MoCA (t = 6.840, P = 0.000) total scores and subtype scores (P = 0.000, for all) in the group with AD were lower than those in the group without AD. Correlation analysis showed that the SCOPA‑AUT score of PD patients with AD was negatively correlated with MMSE and MoCA total scores and subtype scores (P = 0.000, for all). Conclusions The autonomic dysfunction of elderly PD patients with AD is more serious, and the autonomic nervous function is closely related to cognitive function.